Respuesta :
The next step in this problem would be to subtract 12 form both sides. This would result in:
-4x = - 16
Then you would divide each side by -4.
x = 4
This would be your answer.
The correct steps for solving the equation [tex]-4x+12=-4[/tex] are
- Subtract [tex]12[/tex] from both sides and simplify.
- Divide both sides by [tex]-4[/tex], and simplify
To solve the equation below
[tex]-4x+12=-4[/tex]
for [tex]x[/tex], first rearrange the terms so that all [tex]x[/tex] terms are on the LHS, and all numbers are on the RHS. We do this by subtracting [tex]12[/tex] from both sides of the equality. Then we simplify.
[tex]-4x+12-12=-4-12\\-4x=-16[/tex]
Next, we need to remove the co-efficient of [tex]x[/tex] ([tex]-4[/tex]) by dividing both sides with [tex]-4[/tex]. Then we simplify.
[tex]\dfrac{-4x}{-4}=\dfrac{-16}{-4}\\\\x=4[/tex]
Learn more about solving equations here: https://brainly.com/question/13862945